Students' general and physics epistemological beliefs: a twofold phenomenon - BEKİROĞLU, FERAL (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2011)
Background: Although research on epistemological beliefs has expanded over the past two decades, there are still some issues that need to be explored, such as whether epistemological beliefs are domain general or domain specific. Purpose: One of the purposes of this research was to determine if high school students' general epistemological beliefs were different from their epistemological beliefs in the domain of physics. Sample: The research was conducted with 15 grade nine students studying in an urban all-boys school. Their average age was 16. Their previous school experiences were traditional oriented. Design and methods: A case study design with qualitative methods was used for the research. Two questionnaires were developed and used in semi-structured interview protocols two times, within an interval of one semester. The students' epistemological beliefs were categorized as low, medium, high, and very high for each dimension. Conclusions: The following conclusions can be drawn from the study. First, high school students do not have sophisticated general epistemological beliefs in a traditional environment. Second, similarly, high school students' epistemological beliefs in the domain of physics are not sophisticated in a traditional environment. Third, both students' general and physics epistemological beliefs can change and improve to higher levels. However, since beliefs are multidimensional, changes or improvements in one dimension of beliefs do not have to occur in other dimensions. Fourth, the levels of students' beliefs about nature of knowledge in general increase easier than the levels of their beliefs about nature of knowledge in physics. Finally, students' general epistemological beliefs are correlated with their epistemological beliefs in the domain of physics in all dimensions in traditional-oriented approach. However, the correlation decreases in time and it is not possible to mention a domain generality of beliefs when students have constructivist teaching and learning experiences.
Keywords: general epistemological beliefs; physics epistemological beliefs; domain specificity; high school students; PERSONAL EPISTEMOLOGY; ACADEMIC-PERFORMANCE; 1ST YEAR; SCIENCE; KNOWLEDGE; VIEWS